Synergistic Activity of Fosfomycin, Ciprofloxacin, and Gentamicin Against Escherichia coli and Pseudomonas aeruginosa Biofilms - Wang, Lei; Di Luca, Mariagrazia; Tkhilaishvili, Tamta; Trampuz, Andrej; Gonzalez Moreno, Mercedes (Frontiers in Microbiology, 2019)
Gram-negative (GN) rods cause about 10% periprosthetic joint infection (PJI) and represent an increasing challenge due to emergence of antimicrobial resistance. Escherichia coli and Pseudomonas aeruginosa are among the most common cause of GN-PJI and ciprofloxacin is the first-line antibiotic. Due to emergence of fluoroquinolone resistance, we evaluated in vitro the activity of fosfomycin, ciprofloxacin and gentamicin, alone and in combinations, against E. coli and P. aeruginosa biofilms. Conventional microbiological tests and isothermal microcalorimetry were applied to investigate the anti-biofilm activity of the selected antibiotics against standard laboratory strains as well as clinical strains isolated from patients with prosthetic joint associated infections. The biofilm susceptibility to each antibiotic varied widely among strains, while fosfomycin presented a poor anti-biofilm activity against P. aeruginosa. Synergism of two-pair antibiotic combinations was observed against different clinical strains from both species. Highest synergism was found for the fosfomycin/gentamicin combination against the biofilm of E. coli strains (75%), including a gentamicin-resistant but fosfomycin-susceptible strain, whereas the gentamicin/ciprofloxacin combination presented synergism with higher frequency against the biofilm of P. aeruginosa strains (71.4%). A hypothetical bacteriolysis effect of gentamicin could explain why combinations with this antibiotic seem to be particularly effective. Still, the underlying mechanism of the synergistic effect on biofilms is unknown. In conclusion, combinatorial antibiotic application have shown to be more effective against biofilms compared to monotherapy. Further in vivo and clinical studies are required to determine the potential treatment regimen based on our results.